English language and an inclusive Malaysia - Campbell, James (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article seeks to discuss the pressures and forces which define the Malaysian English language debate and suggests that a new social compact involving a renewed commitment to democracy and social justice in Malaysia may be the necessary social context needed to address the increasingly unstable tension between nationalist language concerns and the pressures of globalization. In this article we shall argue that the way to avoid the English language debate from getting stuck oscillating between the Scylla and the Charybdis of nationalist and globalist discourses is to try to move the argument around language to one informed by progressive political economy and democratic theory. This also has the advantage of potentially undermining the politics of social division and cleavage which can derail progressive initiatives such as improvement of English in plural societies such as Malaysia.